2004
DOI: 10.1128/aem.70.10.6210-6219.2004
|View full text |Cite
|
Sign up to set email alerts
|

Flow Sorting of Marine Bacterioplankton after Fluorescence In Situ Hybridization

Abstract: We describe an approach to sort cells from coastal North Sea bacterioplankton by flow cytometry after in situ hybridization with rRNA-targeted horseradish peroxidase-labeled oligonucleotide probes and catalyzed fluorescent reporter deposition (CARD-FISH). In a sample from spring 2003 >90% of the cells were detected by CARD-FISH with a bacterial probe (EUB338). Approximately 30% of the microbial assemblage was affiliated with the Cytophaga-Flavobacterium lineage of the Bacteroidetes (CFB group) (probe CF319a), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 61 publications
2
103
0
3
Order By: Relevance
“…15 to 29% of total counts in the Baltic Sea ), while they are often absent from pelagic marine systems, including sites in the Southern Ocean ) and offshore Arctic Ocean ). However, recent molecular studies have identified marine β-Proteobacteria, notably phylotypes of Nitrosomonas and Nitrosospira (Nold et al 2000, Freitag & Prosser 2004, Sekar et al 2004) at polar ocean sites . β-Proteobacteria have been recorded in lake snow (Weiss et al 1998) and in the freshwater melt pools on Arctic pack ice (Brinkmeyer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…15 to 29% of total counts in the Baltic Sea ), while they are often absent from pelagic marine systems, including sites in the Southern Ocean ) and offshore Arctic Ocean ). However, recent molecular studies have identified marine β-Proteobacteria, notably phylotypes of Nitrosomonas and Nitrosospira (Nold et al 2000, Freitag & Prosser 2004, Sekar et al 2004) at polar ocean sites . β-Proteobacteria have been recorded in lake snow (Weiss et al 1998) and in the freshwater melt pools on Arctic pack ice (Brinkmeyer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…on undisturbed samples of aquifer material, using the fluorescence in situ hybridisation (FISH) method Swiger and Tucker 1996;Wagner et al 2003). It is also possible to use FISH to label specific microbial cells and then sort and count the cells by means of flow cytometry (Sekar et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…An example of this for environmental analysis is combined FISH and Fluorescence Activated Sorting (FISH-FACS) for the detection and sortingbased enrichment of specific cell types from natural samples. Kalyuzhnaya et al (62) used this approach to examine methanotrophic bacteria from lake sediments and Sekar et al (63) used similar methods to investigate the composition of marine bacterioplankton communities. Post-sorting genomic techniques were used in both cases for additional sample characterization (62,63).…”
Section: Combining Fish and Flow Cytometrymentioning
confidence: 99%
“…Kalyuzhnaya et al (62) used this approach to examine methanotrophic bacteria from lake sediments and Sekar et al (63) used similar methods to investigate the composition of marine bacterioplankton communities. Post-sorting genomic techniques were used in both cases for additional sample characterization (62,63). Food applications of FISH-FC include the use of a Pseudomonas-specific DNA probe to detect this spoilage organism in milk (64) and detection of Salmonella spp.…”
Section: Combining Fish and Flow Cytometrymentioning
confidence: 99%